At her majesty's request : an African princess in Victorian England - Myers, Walter Dean, 1937- (New York : Scholastic Press, 1999)
Biography of the African princess saved from execution and taken to England where Queen Victoria oversaw her upbringing and where she lived for a time before marrying an African missionary.
Includes bibliographical references (p. 143).
1070
Accelerated Reader AR
Keywords: Victoria, -- Queen of Great Britain, -- 1819-1901 -- Friends and associates -- Juvenile literature; Victoria, -- Queen of Great Britain, -- 1819-1901 -- Friends and associates; Bonetta, Sarah Forbes, -- b. 1843? -- Juvenile literature; Bonetta, Sarah Forbes, -- b. 1843?; Missionaries' spouses -- Africa, West -- Biography -- Juvenile literature; Africans -- Great Britain -- History -- 19th century -- Juvenile literature; Princesses -- Nigeria -- Oyo State -- Biography -- Juvenile literature; Nigerians -- Great Britain -- Biography -- Juvenile literature; Princesses; Women -- Biography; Great Britain -- Court and courtiers -- History -- 19th century -- Juvenile literature; Great Britain -- Court and courtiers